Disruption of the anterior commissure in Olig2 deficient mice. (23rd November 2022) - Gotoh, Hitoshi; Maruyama, Kohei; Yoshii, Kengo; Yamauchi, Nao; Nomura, Tadashi; Ohtsuka, Satoshi; Shirasaki, Ryuichi; Takebayashi, Hirohide; Ono, Katsuhiko
Abstract: In the present study, we examined neural circuit formation in the forebrain of the Olig2 knockout ( Olig2 ‐KO) mouse model and found disruption of the anterior commissure at the late foetal stage. Axon bundles of the anterior commissure encountered the wall of the third ventricle and ceased axonal extension. L1‐CAM immunohistochemistry showed that Olig2 ‐KO mice lose decussation formation in the basal forebrain. DiI tracing revealed that the thin bundles of the anterior commissure axons crossed the midline but ceased further extension into the deep part of the contralateral side. Furthermore, some fractions of DiI‐labelled axons were oriented dorsolaterally, which was not observed in the control mouse forebrain. The rostral part of the third ventricle was much wider in the Olig2 ‐KO mice than in wild‐type mice, which likely resulted in the delay of midline fusion and subsequent delay and malformation of the anterior commissure. We analysed gene expression alterations in the Olig2 ‐KO mice using a public database and found multiple genes, which are related to axon guidance and epithelial‐mesenchymal transition, showing subtle expression changes. These results suggest that Olig2 is essential for anterior commissure formation, likely by regulating multiple biological processes. Abstract : The Olig2 ‐KO mouse shows the defect in the anterior commissure (AC), delayed formation of the decussation or abnormal dorsal orientation of AC axons. The wider rostral third ventricle (3v) may be related to the defects of AC in the KO mouse. Microarray analysis shows the altered expression of genes related to axon guidance and epithelial mesenchymal transition in the Olig2 ‐KO mouse.